2002
DOI: 10.4049/jimmunol.168.8.3992
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Are Required for Primary Immunity in C57BL/6 Mice Following Low-Dose, Intradermal Challenge withLeishmania major

Abstract: Standard murine models of cutaneous leishmaniasis, involving s.c. inoculation of large numbers of Leishmania major promastigotes, have not supported an essential role for CD8+ T cells in the control of primary infection. Recently, a L. major model combining two main features of natural transmission, low parasite dose and inoculation into a dermal site, has been established in resistant C57BL/6 mice. In the present studies, C57BL/6 mice with CD8+ T cell deficiencies, including CD8−/− and CD8-depleted mice, fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
253
1
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(266 citation statements)
references
References 52 publications
8
253
1
4
Order By: Relevance
“…8). While CD4 + Th1 cells are involved in the host defense against L. major [1], CD8 + T cells recruited to the site of infection also play a critical role in resolution of primary L. major infection [43,44]. Furthermore, CXCR3 has been shown to facilitate trafficking of CD8 + T cells into the site of inflammation [26,45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8). While CD4 + Th1 cells are involved in the host defense against L. major [1], CD8 + T cells recruited to the site of infection also play a critical role in resolution of primary L. major infection [43,44]. Furthermore, CXCR3 has been shown to facilitate trafficking of CD8 + T cells into the site of inflammation [26,45].…”
Section: Resultsmentioning
confidence: 99%
“…Cells from the ear lesions of L. major-infected CXCR3 -/-and CXCR3 +/+ mice were isolated as described previously [43]. Briefly, two sheets of ear were separated and incubated with dermal side down on complete RPMI 1640 at 37 C for 6 h. The cells spontaneously migrating out of the dermis were collected and filtered through 70-lm pore size cell strainer for flow cytometric analysis.…”
Section: Isolation Of Cells From the Ear Lesions And Phenotypic Analymentioning
confidence: 99%
“…In contrast, antibodymediated depletion of CD8 + T cells transiently increased the severity of footpad lesions in high dose-infected mice [33]. In the low-dose ear infection model both CD8 -/-and anti-CD8-treated mice developed chronic lesions with high parasite burden [34]. Based on these results, the functional blockade of Tyk2 -/-CD8 + T cells observed in our study is likely to contribute to the disease aggravation observed in Tyk2 -/-mice.…”
Section: Tyk2 and T Cellsmentioning
confidence: 94%
“…However, limited information is available regarding the molecular details as to how DCs respond to the intracellular amastigotes. As professional APCs and potential targets for Leishmania infection, DCs play multiple roles in leishmaniasis: updating/transporting parasites (Moll et al, 1995), initiating innate immunity (Schleicher et al, 2007), priming parasitespecific CD4 + and CD8 + T cells, and maintaining T cell memory/activity (Baldwin et al, 2004;Belkaid et al, 2002;Bertholet et al, 2005;Zaph et al, 2004). Recently, DC-based vaccination for the control of L. major-induced cutaneous leishmaniasis has gained special attention (Ramirez-Pineda et al, 2004;Remer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%